PERBEDAAN PENINGKATAN PRESTASI BELAJAR BIOLOGI DITINJAU DARI PEMANFAATAN MEDIA - Ernila Isneni; Herpratiwi Herpratiwi; Rini Rita Marpaung (Indonesia Journal of Educational Technology, 2013)
The objectives of this research are to explain : 1) the interaction of learning style and the using of instructional media toward students achievement, 2) the difference of the students achievement on visual learning style by using CD interactive media and model.The research was done in SMAN 1 Pringsewu. The data was collected by using questionnaire and test. And the data was analyzed by using ANAVA and T-test.The conclusion of the research are ; 1) there is an interaction between instructional media and learning style toward students achievement, in which the instructional media given both by CD interactive media and the model have effect one to another. And it was also influenced by aspect of learning style with Fhitung is28,684 > F table 2,19, 2) the increase of students achievement on visual learning style by using CD interactive media is higher than those on visual learning style using model media, with the gain average 0,340 compared with the model 0,295.Tujuan penelitian ini untuk menjelaskan:1) interaksi antara gaya belajar dan penggunaan media pembelajaran terhadap prestasi belajar siswa, 2) perbedaan peningkatan prestasi belajar siswa dengan gaya belajar visual yang memanfaatkan media CD interaktif dan model. Penelitian dilaksanakan di SMA N 1 Pringsewu. Data dikumpulkan dengan menggunakan angket dan tes dan di analisis menggunakan ANAVA dan uji t.Kesimpulan penelitian adalah: 1) terdapat interaksi antara media pembelajaran dan gaya belajar terhadap prestasi belajar siswa,dimana peningkatan prestasi belajar siswa dipengaruhi oleh media pembelajaran dan gaya belajar, dengan Fhitung sebesar 28,684 > F tabel 2,19; 2) peningkatan prestasi belajar belajar siswa dengan gaya belajar visual yang memanfaatkan media CD interaktif lebih tinggi daripada siswa dengan gaya belajar visual yang memanfaatkan media model, dengan rata-rata gain sebesar 0,340 dibandingkan model yang hanya 0,295.Kata kunci : CD interaktif , prestasi biologi, visual, kinestetik, model.